1997
DOI: 10.1074/jbc.272.43.27058
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Studies on Substrate Structure Requirements of Glycoamidases A and F

Abstract: Glycoamidases (peptide-N 4-(N-acetyl-␤-glucosaminyl)-asparagine amidase, EC 3.5.1.52; also known as peptide: N-glycanases (PNGases) release N-linked oligosaccharides from glycopeptides and/or glycoproteins by hydrolyzing the glycosylated ␤-amide bond of the asparagine side chain. The most widely used glycoamidases are those from Flavobacterium meningosepticum (glycoamidase F or PNGase F) and almond emulsin (glycoamidase A or PNGase A). To study the substrate structure requirement of these enzymes systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 47 publications
(32 reference statements)
6
55
0
Order By: Relevance
“…Altmann et al (27) showed that the size of the carbohydrate moiety in the substrate has little influence on the enzymatic activities of N-glycosidase and that the hydrolysis rates of PNGase enzymes are primarily determined by the length of the peptide. Studies on the substrate requirements of PNGase F showed that Asn-linked GlcNAc occupied the most critical position for substrate binding and that PNGase F requires at least the di-N,NЈ-acetylchitobiosyl core unit and a tripeptide for its activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…Altmann et al (27) showed that the size of the carbohydrate moiety in the substrate has little influence on the enzymatic activities of N-glycosidase and that the hydrolysis rates of PNGase enzymes are primarily determined by the length of the peptide. Studies on the substrate requirements of PNGase F showed that Asn-linked GlcNAc occupied the most critical position for substrate binding and that PNGase F requires at least the di-N,NЈ-acetylchitobiosyl core unit and a tripeptide for its activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…Lectins are able to recognize structures as varied as the monosaccharides sialic acid (28) and fucose (29), and higher-order structures such as the Tn (30) and sialyl-Tn tumor antigens (31) and the conserved core region of N-glycans (32). However, lectins typically have low affinity for their glycan epitope and require multivalency for high-avidity binding (33).…”
Section: Imaging Glycans With Lectins and Antibodiesmentioning
confidence: 99%
“…Of these few predicted sites, only those in AGP-like glycoproteins of tobacco styles have been shown to be actually glycosylated, as judged by sensitivity to glycoamidase F (36,37). As a test for the presence of N-glycans, rose CM-AGPs were treated with glycoamidase A, which cleaves a broader range of substrates than glycoamidase F (38). For example, plant glycoproteins with N-glycans containing Fuc linked ␣1 3 3 to the innermost GlcNAc are cleaved by glycoamidase A but are highly resistant to glycoamidase F (39).…”
Section: Table III Chemical Analysis Of Glycolipids Copurifying With mentioning
confidence: 99%